Practice in industry training in fish preservation. - Moralde, Nunilon C. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1963)
Fish is safely considered as the most important product of the sea. To the Filipinos and other oriental people, fish as food is the counterpart of rice in their diet. It is not only the cheapest but also the widely distributed source of much needed food elements. In the true sense of the food, food is very nutritious. Today, several methods are in existence and most of them are employed in fish preservation in our fishing industry. Needless to say this is a good sign of progress achieve by our technologists in this field of endeavour. The college of fisheries of the university of the Philippines, for example has been playing an important role in training students, both theoretically and practically, on his particularly chosen field or work. Surely, by this, move, the next generation on is faced with a bright future in so as fish preservation is concerned. This report is a compilation made my the author a product of her four months practice in industry on several methods employed for fish preservation through actual practice and on-the-spot observations. To make thoroughly useful, the author did her very best to present various useful methods or information in a step by step, from which, she hopes as expressed in a layman's language, could easily be understood. It is the result of the author's attempt, with the best of her knowledge, in printing a book of her own by-line and accomplishments, that shall be of a simple guide to the collegian in general and serve the purpose of a satisfactory fulfilment of the requirements for graduation. It is therefore e earnestly hoped that the contents of this book will prove interesting and helpful, like any individual, the author humbly suggests the reader's constructive criticism that might as well broaden public opinion in this particular subjects matter discussed.
Keywords: Fish-Preservation.